Predictor value of the inflammation biomarkers regarding the post-infarction remodeling of myocardium - M. V. Ivanov; M. I. Popovich; L. M. Cheban; I. M. Popovich; V. M. Ivanov; V. A. Kobets (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To study the trait of the changes of circulating level of pro- and antiinflammatory biomarkers as well as metalloproteinase 8 (MMP-8) in the first 7 days after revascularization in patients with acute myocardial infarction with ST segment elevation (STEMI) for assessment of their prognostic value regarding post-infarction remodeling pattern.Material and methods. In 113 patients with STEMI which developed in 5 months after angioplasty adaptive myocardium remodeling (AMR) (n=56) or pathological myocardium remodeling (PMR) (n=57), determined by enzyme-linked immunosorbent assay (ELISA) method daily serum concentration of pro-inflammatory ((high sensitive C reactive protein, interleukins (IL) 1, 6, tumor necrosis factor alpha and monocyte chemoattractant protein 1)), anti-inflammatory biomarkers (IL-4, IL-10, IL-33, IL-1 receptor antagonist and heregulin-1beta) аs well as ММР-8 in the first 7 days after myocardium revascularization. According to clinic-demographic indices both groups were comparable. Obtained data have been compared with results of 20 healthy persons (control group).Results. The dynamics of pro-inflammatory biomarkers did not differ in patients with AMR and PMR after revascularization. It was characterized by a significant biomarker increase at 3-rd day followed by a decline toward 7-th day up to initial level. Among anti-inflammatory biomarkers IL-4 and IL-10 have manifested by a distinct dynamic in concern to myocardial remodeling pattern. In both groups these interleukins decreased after angioplasty, reaching a minimal level at 3-rd day. However, in patients with AMR since 4-th day has been established an increase of serum content of IL-4 and IL-10, their increment being at 7-th day in a range of 52-55% (p<0,05). In patients with PMR the interleukins rise was negligible: 5,7-5,8%. MMP-8 dynamics also has been different in groups and was correlated with dynamics of IL-4 and IL-10. Thus, in patients with AMR its level has fallen since 4-th day up to 7-th day by 46,6%, while in group with PMR metalloproteinase level in this period practically did not change, remaining significantly higher than control by 45-53%.Conclusion. In our study the serum content of main pro-inflammatory biomarkers (hsCRP, IL-1, IL-6, TNF-ɑ) didn’t differ in the first 7 days after revascularization in patients with adaptive and pathological postinfarction remodeling of myocardium, and thus don’t have predictive value concerning the remodeling pattern. Among anti-inflammatory cytokines dynamics of IL-4 and IL-10 differed in dependence on remodeling pattern. Their significant elevation by 52-55% from 4th up to 7th day after angioplasty was established in patients with adaptive myocardium remodeling, while in PMR their level didn’t change during this period that can emphasize their prognostic value. The character of MMP-8 change is pathogenetically correlated with dynamics of IL-4 and IL-10.